PERFORMANCE MODELING OF UNSIGNALED INTERSECTIONS USING THE VISSIM SOFTWARE - Sarwanta, Sarwanta; Hamdani Abdulgani (Jurnal Riset Sosial Humaniora dan Pendidikan, 2022)
A level road intersection is a meeting place for vehicle flows from various directions both towards the intersection and leaving the intersection, so that at the intersection there is the potential for vehicle conflicts to occur which are at the same time at the same point. This causes the vehicle to reduce speed. Reducing vehicle speed at intersections results in the potential for queues and delays. Evaluation of the performance of the intersection needs to be done to find out the current performance of the intersection, so that anticipatory steps can be taken so that the performance of the intersection can be maintained and maintained in good condition. In this study, an analysis of intersection performance will be carried out using the Vissim software. In this study, an assessment of the unsignalized intersection of Pasar Butun, Balikpapan City was carried out. The data needed for input into the model include traffic flow data at rush hour or peak density hours, intersection geometry data. The output or results generated by the model are intersection performance information in the form of queue length and delay time parameters  Degree of Saturation (DS) for the existing condition is 1.70 and for the next 5 years it is 2.20. Parameters of queue length and time delay in existing conditions are 33.0 m and 3.65 sec/pcu and for the next 5 years projection are 87 m and delay time is 187.s/pcu